Capsule-dependent impact of MAPK signalling on host cell invasion and immune response during infection of the choroid plexus epithelium by Neisseria meningitidis - Herold, Rosanna; Scholtysik, René; Moroniak, Selina; Weiß, Christel; Ishikawa, Hiroshi; Schroten, Horst; Schwerk, Christian (Fluids and barriers of the CNS, 2021)
Background:  The Gram-negative bacterium Neisseria meningitidis (Nm) can cause meningitis in humans, but the host signalling pathways manipulated by Nm during central nervous system (CNS) entry are not completely understood. - Methods:  We investigate the role of the mitogen-activated protein kinases (MAPK) Erk1/2 and p38 in an in vitro model of the blood-cerebrospinal fluid barrier (BCSFB) based on human epithelial choroid plexus (CP) papilloma (HIBCPP) cells during infection with Nm serogroup B (NmB) and serogroup C (NmC) strains. A transcriptome analysis of HIBCPP cells following infection with Nm by massive analysis of cDNA ends (MACE) was done to further characterize the cellular response to infection of the barrier. - Results:  Interestingly, whereas NmB and NmC wild type strains required active Erk1/2 and p38 pathways for infection, invasion by capsule-deficient mutants was independent of Erk1/2 and, in case of the NmB strain, of p38 activity. The transcriptome analysis of HIBCPP cells following infection with Nm demonstrated specific regulation of genes involved in the immune response dependent on Erk1/2 signalling. Gene ontology (GO) analysis confirmed loss of MAPK signalling after Erk1/2 inhibition and revealed an additional reduction of cellular responses including NFκB and JAK-STAT signalling. Interestingly, GO terms related to TNF signalling and production of IL6 were lost specifically following Erk1/2 inhibition during infection with wild type Nm, which correlated with the reduced infection rates by the wild type in absence of Erk1/2 signalling. - Conclusion:  Our data point towards a role of MAPK signalling during infection of the CP epithelium by Nm, which is strongly influenced by capsule expression, and affects infection rates as well as the host cell response.